2022
DOI: 10.1155/2022/5718341
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Air-Borne and Surface-Borne Bacterial Pathogens and Their Antimicrobial Profiles in Wolaita Sodo, Southern Ethiopia

Abstract: Background. It is well documented that hospital environments are the niche/reservoir of many clinically important microorganisms, including multidrug-resistant air-borne and surface-borne pathogens. This problem is the most pressing public health concern, particularly in developing countries like Ethiopia, due to its poor infection management system. This study was planned to detect air-borne and surface-borne bacterial pathogens and their antimicrobial resistance patterns in Wolaita Sodo University Comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…This finding was consistent with the results of Claire E. Adams and colleagues 20 , that assessed the transmission of Staphylococcus aureus in the air and surfaces of the intensive care unit (ICU) and delivery rooms. Also, our findings are consistent with the results of Chemere Madebo et al,'s study, regarding the relationship between the distribution of Staphylococcus aureus in the air of ICU wards and operating rooms of hospitals in southern Ethiopia with hospital infections 20 , 21 .…”
Section: Discussionsupporting
confidence: 93%
“…This finding was consistent with the results of Claire E. Adams and colleagues 20 , that assessed the transmission of Staphylococcus aureus in the air and surfaces of the intensive care unit (ICU) and delivery rooms. Also, our findings are consistent with the results of Chemere Madebo et al,'s study, regarding the relationship between the distribution of Staphylococcus aureus in the air of ICU wards and operating rooms of hospitals in southern Ethiopia with hospital infections 20 , 21 .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the study identified the presence of K. pneumoniae in 1.8% of the samples. Although the proportion may be relatively lower compared to other pathogens, the detection of K. pneumoniae is still significant due to its potential to cause serious infections and its association with antibiotic resistance [41]. In the study conducted by Madebo et al, P. aeruginosa and K. pneumoniae were reported as the leading contaminants in the hospital as well [41].…”
Section: Overall Sketch Of Microbial Profile In the Hospital Indoor E...mentioning
confidence: 99%
“…Although the proportion may be relatively lower compared to other pathogens, the detection of K. pneumoniae is still significant due to its potential to cause serious infections and its association with antibiotic resistance [41]. In the study conducted by Madebo et al, P. aeruginosa and K. pneumoniae were reported as the leading contaminants in the hospital as well [41]. However, another dominating pathogen of S. aureus did not appear in our study which could potentially be attributed to a low mapping rate at the species level during the analysis.…”
Section: Overall Sketch Of Microbial Profile In the Hospital Indoor E...mentioning
confidence: 99%